2017
DOI: 10.3762/bjoc.13.128
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY-based fluorescent liposomes with sesquiterpene lactone trilobolide

Abstract: Like thapsigargin, which is undergoing clinical trials, trilobolide is a natural product with promising anticancer and anti-inflammatory properties. Similar to thapsigargin, it has limited aqueous solubility that strongly reduces its potential medicinal applications. The targeted delivery of hydrophobic drugs can be achieved using liposome-based carriers. Therefore, we designed a traceable liposomal drug delivery system for trilobolide. The fluorescent green-emitting dye BODIPY, cholesterol and trilobolide wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…10 To overcome these limitations, a number of supramolecular-based strategies have been developed. [11][12][13][14][15][16][17] Complementary to these efforts, researchers have utilized protein-based hybridization strategies (host-guest assembly) as a means to overcome the poor solubility and enhance the imaging capability of a contrast agent used in bioimaging applications. 18,19,39 We thus envisaged that judicious design of an appropriate uorescent probe-protein complex might permit enhanced sensitivity towards the detection of a disease-specic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…10 To overcome these limitations, a number of supramolecular-based strategies have been developed. [11][12][13][14][15][16][17] Complementary to these efforts, researchers have utilized protein-based hybridization strategies (host-guest assembly) as a means to overcome the poor solubility and enhance the imaging capability of a contrast agent used in bioimaging applications. 18,19,39 We thus envisaged that judicious design of an appropriate uorescent probe-protein complex might permit enhanced sensitivity towards the detection of a disease-specic biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a drug delivery system for potential theranostic applications, Škorpilová et al synthesized the fluorescent macrostructure 23 containing sesquiterpene lactone trilobolide (Tb), cholesterol, and a green-emitting boron dipyrromethene (BODIPY) dye. The synthesis of compound 23 involved a three-step sequence, starting from the CuAAC reaction of propargyl cholesterol 20 with BODIPY dye 21 , followed by functionalization with sesquiterpene lactone trilobolide (Scheme 6) [11]. This fluorescent cholesterol conjugate 23 was successfully incorporated into liposome formulations, which showed promising immunomodulatory properties in primary rat macrophages and improved drug distribution in U-2 OS and HeLa cancer cells.…”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…The study of the intracellular trafficking pattern of liposomes revealed two populations: One localized on the cell membrane and the other inside the cell, this last one closely related to cell death. This new liposomal cholesterol conjugate 23 not only retains the biological properties of pure trilobolide, but also enhances bioavailability, and thus has potential for use in theranostic applications [11].…”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…The inhibition of P-gp can enhance the intracellular accumulation of anticancer drugs which are usually substrates of P-gp, including anthracyclines and vinca alkaloids [ 5 , 6 ]. Alternatively, to solve these problems, biochemical and physical methods as well as nanotechnologies are used to overcome MDR [ 2 , 7 ], such as microRNA and RNA interference, monoclonal antibodies targeting P-gp, polymeric nanoparticles, micelles, and liposome nanoparticles. Liposome nanoparticles are the most developed and widely applied technique, the applications of which can be observed in the FDA-approved nanodrugs Doxil ® and DaunoXome ® [ 8 ].…”
Section: Introductionmentioning
confidence: 99%